Isolation, replication of Brucella OMP31 gene and transfering to an expression vector - Resalehpour, Shima; Mousavi-Niri, Neda; Mahdavi, Morteza; Aliheydari, Elahe; Davood Hosseini, Seyed (Journal of Biological Studies, 2022)
Brucellosis is a chronic and debilitating disease that affects various organs and has many negative consequences in the field of health and economy in Iran. Brucella outer membrane proteins, especially OMP31, OMP28, are important in vaccine design, production of required antigens, serum diagnostics, production of safe recombinant proteins with appropriate immunogenicity, and cost-effective production. Selecting the appropriate expression and hosting system for the expression of these recombinant proteins that can be produced safely, massively and economically is one of the main priorities in the production of vaccines and antigens used. In this study, plasmid pnz8149 was extracted from Lactococcus lactis. Brucella OMP31 gene was then amplified into specific vectors after amplification with specific primers and digestion of nco1 and bmh1 enzymes. Using electroporation, the plasmid containing the gene was transferred to Lactococcus lactis. In order to select transformant lactococci, lactococci containing recombinant plasmid pNZ8149 + OMP31 were transferred to Elliker medium. Finally, the presence of recombinant plasmid pNZ8149 + OMP31 in Lactococcus lactis was investigated by PCR, enzymatic digestion and sequencing. The quantity and purity of pnz8149 extracted plasmid were 123.8 ng and 1.93 μg, respectively. Due to the design of specific primers for amplification of OMP31 gene of this fragment, the target of Brucella bacterium genome was successfully amplified to 723 bp. OMP31 gene insertion in pnz8149 vector was successfully performed and the presence of recombinant plasmid pNZ8149 + OMP31 in Lactococcus lactis was confirmed. Given that the product of the OMP31 gene is a valuable candidate for the production of vaccine, this gene can be of significant target in research associated with vaccine production for treatment of brucellosis.